2009
DOI: 10.1242/jeb.028704
|View full text |Cite
|
Sign up to set email alerts
|

Water exchange and permeability properties of the skin in three species of amphibious sea snakes (Laticauda spp.)

Abstract: SUMMARYEvolutionary transitions between different environmental media such as air and water pose special problems with respect to skin permeability because of the dramatic changes in the driving gradients and nature of water exchange processes. Also, during the transitional periods prior to complete adaptation to a new medium, the skin is exposed to two very different sets of environmental conditions. Here, we report new data for transepidermal evaporative water loss (TEWL) and cutaneous resistance to evaporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 34 publications
1
39
0
Order By: Relevance
“…Mean rates of mass loss in L. semifasciata and N. fasciata were similar to those previously reported for these species (Dunson, 1978;Lillywhite et al, 2009), whereas estimates in N. c. clarkii were slightly higher than previously reported (Dunson, 1980;Pettus, 1963). Among-individual variation in mean daily mass loss was very high in both species of Nerodia, likely reflecting the large overall range in body mass in these two species, and mass loss did not differ among treatments in any of the species examined.…”
Section: Discussionsupporting
confidence: 84%
“…Mean rates of mass loss in L. semifasciata and N. fasciata were similar to those previously reported for these species (Dunson, 1978;Lillywhite et al, 2009), whereas estimates in N. c. clarkii were slightly higher than previously reported (Dunson, 1980;Pettus, 1963). Among-individual variation in mean daily mass loss was very high in both species of Nerodia, likely reflecting the large overall range in body mass in these two species, and mass loss did not differ among treatments in any of the species examined.…”
Section: Discussionsupporting
confidence: 84%
“…It is customary to calculate Dwvp as the difference between wvp at 100% RH and ambient T a and wvp at ambient RH and T a [7,14,20]. Skin temperature is more appropriate than T a to calculate Dwvp [16], but its measurement is more difficult, so ambient temperature is generally used as a proxy. The Dwvp will be similar, particularly at low ambient wvp, unless there is a very large difference between T a and T skin .…”
Section: (B) Respirometrymentioning
confidence: 99%
“…This raises the important question of whether these endotherms have physiological regulation of EWL at low and moderate T a , which could confer substantial advantages for balancing their water budget. However, complexities with these studies, such as use of RH, wvp or Dwvp, heterothermy [13], postural adjustments [14], measurement method and protocols [13,15], and use of skin or ambient temperature to calculate Dwvp [16] make it difficult to interpret these patterns.…”
Section: Introductionmentioning
confidence: 99%
“…The surface energy of snake skin has been mostly assumed according to the chemical analysis of the skin material [14–18]. Only Lillywhite et al [19] directly measured contact angles of the snake skin and showed its hydrophobic properties. The mechanical properties of the skin have been investigated in great detail by Klein and Gorb [20].…”
Section: Introductionmentioning
confidence: 99%